2017
DOI: 10.1016/j.cellsig.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of paroxetine on proximal β-adrenergic receptor signaling

Abstract: β-adrenergic receptors (βAR) regulate numerous functions throughout the body, however G protein-coupled receptor kinase (GRK)-dependent desensitization of βAR has long been recognized as a maladaptive process in the progression of various disease states. Thus, the development of small molecule inhibitors of GRKs for the study of these processes and as potential therapeutics has been at the forefront of recent research efforts. Via structural and biochemical analyses, the selective serotonin reuptake inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The exception seems to be paroxetine which inhibits isolated GRK2 with an IC50 of 1.38 μM (Waldschmidt et al, 2016), and GRK2-mediated 2AR phosphorylation in HEK293 cells with an IC50 is 5.9 μM (Guo et al, 2017), which is similar to our findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The exception seems to be paroxetine which inhibits isolated GRK2 with an IC50 of 1.38 μM (Waldschmidt et al, 2016), and GRK2-mediated 2AR phosphorylation in HEK293 cells with an IC50 is 5.9 μM (Guo et al, 2017), which is similar to our findings.…”
Section: Discussionsupporting
confidence: 82%
“…In support of these observations paroxetine has previously been shown to inhibit GRK2-mediated phosphorylation of thyrotropin releasing hormone receptor with an IC50 of 30 µM (Thal et al, 2012), and to enhance AR-mediated cardiomyocyte contraction (a process negatively regulated by GRK2) (Thal et al, 2012). Recently, paroxetine has been shown to inhibit 2-receptor desensitization by blocking GRK2-mediated adrenoceptor phosphorylation and arrestin recruitment (Guo et al, 2017). Collectively, these data further support the notion that paroxetine selectively interacts with GRK2 to inhibit its ability to desensitize GPCR signalling.…”
Section: Discussionmentioning
confidence: 56%
“…Our results are consistent with other recent studies on the ability of paroxetine to inhibit phosphorylation of the b2AR and reduce internalization of the b1 and b2ARs in HEK293 and U2OS cells, respectively (Guo et al, 2017), thus demonstrating the utility of paroxetine analogs for inhibiting the proximal effects of GRKs in multiple cell types for multiple GPCRs. An assay for cell permeability similarly showed that paroxetine-based inhibitors in general also demonstrated better cell permeability properties than the GSK180736A scaffold ( Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…The importance of β-arrestin for the signalling of β 2 AR was demonstrated by influences of paroxetine, a GRK2 inhibitor, on β 2 -adrenergic signal transduction. Guo et al observed that paroxetine inhibits the isoprenaline-induced phosphorylation of β 2 AR, the recruitment of β-arrestin2, and the subsequent receptor internalization 19 . In our experiments paroxetine pre-treated and isoprenaline stimulated HEK SNAP-β 2 wild-type cells changed the occupancy of S1 from 16.0 % to 15.8 %, S2 from 51.7 % to 54.0 % and S3 from 32.3 % to 30.2%, which was not significant (Figure 4).…”
Section: Figurementioning
confidence: 99%